The difficulties of teaching GIS in higher education institutions during wartime - Stefan Molnar D.; Molnár D. István; Молнар Д. Стефан (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Purpose of the research. This study investigates how armed conflict reshapes the conditions, content, and conduct of Geographic Information Systems (GIS) education in higher education, with a primary focus on the Ukrainian context. We examine the compounded effects of infrastructure disruption, displacement, psychological stress, constrained access to geodata and software, and heightened ethical and security risks on the integrity of practice-oriented GIS learning. Beyond diagnosing barriers, the study seeks to identify strategies that preserve core learning outcomes, professional socialization, and academic quality amid extreme volatility. Statement of objectives. The article pursues six interlocking objectives: (1) to map the multi-level constraints—material, technological, pedagogical, psychosocial, and normative—affecting GIS education during wartime; (2) to document the specific mechanisms by which power outages, unstable connectivity, damaged laboratories, curfews, and campus closures degrade experiential learning and assessment; (3) to assess how student and staff displacement, mobilization, and trauma fragment cohorts, extend time-to-degree, and reduce feedback density; (4) to evaluate the feasibility of offlinefirst, low-bandwidth teaching models using open-source software, portable distributions, and compact didactic datasets; (5) to develop an operational ethics framework for spatial teaching under conflict conditions, including risk assessment for sensitive locations and data minimization in coursework and dissemination; and (6) to identify the role of international collaborations, humanitarian mapping projects, and policy flexibilities in sustaining learning continuity and quality assurance. Methodological approach and its purpose. Methodologically, the paper integrates (a) a structured workflow analysis of the GIS teaching sequence—data acquisition, preparation, analysis, visualization, and communication—with (b) evidence from institutional practice in wartime universities and (c) a targeted review of literature on emergency higher education, remote/lowresource GIS instruction, and geospatial ethics. The workflow analysis “stress-tests” each instructional stage against wartime perturbations (e.g., denial of access to state geodatabases; cyberattacks or throttling of cloud services; hardware constraints on student devices; intermittent electricity). The purpose is twofold: first, to generate a granular causal map of failure points that is actionable for contingency planning and accreditation; second, to validate which adaptations— portable QGIS deployments, pre-rendered rasters, modular micro-projects, scripted labs with printable step-by-steps, asynchronous assessment with screenshot portfolios—maintain essential competencies when standard facilities and bandwidth are unavailable.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: wartime education; GIS pedagogy; higher education; offline-first instruction; geospatial ethics